Efektifitas Cinema Therapy untuk Meningkatkan Kepercayaan Diri Anak Korban Perceraian Orang Tua - Salis Khoiriyati; Eka Rizki Amalia (Aulada : Jurnal Pendidikan dan Perkembangan Anak, 2019)
This study aims to find out how effective cinema therapy is to increase parents' trust. in this study, subjects were given intervention by showing several films that had a storyline that was almost the same as the subject's life. in the film there is a motivation that there is nothing to worry about from parents' divorce. In addition, psychoeducation is also given to families who care for children who are victims of divorce